2022
DOI: 10.1155/2022/8979904
|View full text |Cite
|
Sign up to set email alerts
|

α-Lipoic Acid-Plus Ameliorates Endothelial Injury by Inhibiting the Apoptosis Pathway Mediated by Intralysosomal Cathepsins in an In Vivo and In Vitro Endothelial Injury Model

Abstract: α-Lipoic acid-plus (LAP), an amine derivative of α-lipoic acid, has been reported to protect cells from oxidative stress damage by reacting with lysosomal iron and is more powerful than desferrioxamine (DFO). However, the role of LAP in experimental carotid artery intimal injury (CAII) has not yet been well investigated. Therefore, we sought to uncover the role and potential endovascular protective mechanisms of LAP in endothelial injury. In vitro, oxyhemoglobin (OxyHb) stimulation of cultured human umbilical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Mechanical damage caused by angioplasty can arouse severe oxidative stress, leading to impaired reendothelialization process. [ 16 ] To simulate this process in vitro, we incubated human aortic endothelial cells (HAECs) with various concentrations of H 2 O 2 for 24 h and assessed cell viability (Figure S3 , Supporting Information). The results indicated that a concentration of 100 µM H 2 O 2 was suitable for inducing oxidative stress damage to HAECs, and hence this concentration was chosen for subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical damage caused by angioplasty can arouse severe oxidative stress, leading to impaired reendothelialization process. [ 16 ] To simulate this process in vitro, we incubated human aortic endothelial cells (HAECs) with various concentrations of H 2 O 2 for 24 h and assessed cell viability (Figure S3 , Supporting Information). The results indicated that a concentration of 100 µM H 2 O 2 was suitable for inducing oxidative stress damage to HAECs, and hence this concentration was chosen for subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Serum CTSB levels were strongly related to cardiovascular events in stable coronary heart disease patients (64) So when the treatments have been given to the diabetic rats the release of cathepsin B declined significantly (as it's clear from the highlighted brown area) after four weeks in comparison with the N groups and restored to near normal which means that they decreased the cardiomyopathic change effectively. Moreover, treatment groups in which ALA has been added provided a better reduction on the level of cathepsin B because ALA inhibited intraliposomal Cathepsin-mediated apoptosis by chelating excess iron in endothelial lysosomes after intimal damage (65).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the lipoylation pathway has been demonstrated to lead to mitochondrial dysfunction in ECs, impairing vascular growth and development in mouse models[ 37 ]. Studies have also shown that α-lipoic acid-plus exerts endovascular protective effects by reducing mitochondrial damage and helping to maintain lysosomal integrity, inhibiting the apoptosis pathway post intimal injury [ 38 , 39 ]. Considering the roles of copper metabolism and aberrant protein lipoylation in the vascular endothelium, along with the characteristics of abnormal vascular development and a tendency for recurrent hemorrhages in CCMs, we are speculating on whether cuproptosis are involved in the pathogenesis and development of CCMs.…”
Section: Introductionmentioning
confidence: 99%